The phenomenon of superparasitism in Trichogramma evanescens minutum Riley - I (Hymenoptera: Trichogrammatidae). - Chacko, M. J. (Contributions to Entomology = Beiträge zur Entomologie, 1969)
When superparasitism occurs in Trichogramma evanescens minutum there is a recuction in fecundity, longevity, and size. If two parasites belonging to the opposite sexes emerge from a superparasitised egg of Corcyra cephalonica, then the fecundity, longevity, and size of the female are less than those of either of the females that emerge from an egg. It appears that the male has a quicker rate of absorption of nourishment in the larval stages, and this coupled with ist lesser food requirements enables it to complete the development, leaving very little food for the female. In severe cases of superparasitism the quicker food absorption by the males results in the elimination of the females, thus accounting for the preponderance of males. When defective forms are produced as a result of superparasitism, there is a further reduction in fecundity and longevity.